Creating the Nation on the Page: The Imagined Nationhood in Raja Rao’s Kanthapura - TURAN, AYŞEGÜL (Namık Kemal Üniversitesi, Fen-Edebiyat Fakültesi Dekanlığı, 2021)
Raja Rao’s Kanthapura (1938) focuses on the story of how Gandhian ideology reachesthe village of Kanthapura and changes the villagers’ lives drastically. Rao’s portrayalof national identity, by putting the village in the center, relies heavily on the use ofcenturies-old Indian culture and traditions in order to create a sense of shared historyand collective sense of belonging against British colonialism. In the novel, thevillagers re-discover their shared cultural and religious past in their attempt to find thestrength to fight against colonial domination and envision a new society. Thus, thenarrative’s imagining of the future society follows a past-oriented trajectory, namelycombining the past, present and future in the microcosmos of the village. I contendthat the temporal origin of the projected nationhood determines the limitations andpossibilities for the formation of the idea of nation and the future society.
Ulusu Sayfaya Taşımak: Raja Rao’nun Kanthapura Adlı Eserinde Ulus Tahayyülü
Keywords: Postcolonial Literature; India; National Culture; Raja Rao; Kanthapura